Factors That Affect Oral Care Outcomes for Institutionalized Elderly - Yoshiaki Nomura; Noriko Takei; Takanori Ishii; Koji Takada; Yasuharu Amitani; Hitomi Koganezawa; Shizuko Fukuhara; Keita Asai; Ryuji Uozumi; Kazuhisa Bessho (International Journal of Dentistry)
The aim of this study was to evaluate the effect of an oral care intervention program on the incidence of pneumonia and fever as a surrogate endpoint. In addition, we tried to determine the oral care risk factors for the incidence of fever. We provided an oral care program for the elderly at one private nursing home in July 2013. The maximum capacity of the nursing home was 60 residents. The body temperatures of all residents were measured twice a day and were summarized as the incidence of fever over a one-month period, which was used as the dependent variable. The residents’ life conditions, number of teeth, and prescribed diet were used as independent variables. The factors that affected the incidence of fever were the number of remaining teeth, a prescribed diet of sliced food, the meal care level, and the oral Candida levels. These risk factors affected the incidence of fever independently or interactively with oral care. Some risk factors for the incidence of fever were enhanced by the oral care program. It is important to evaluate and control these factors before the implementation of an oral care program.